Implementasi manajemen strategi pada lembaga keuangan syariah untuk meningkatkan daya saing di era digital - aliyana, ama dwi (Maliki Interdisciplinary Journal, 2025)
The rapid advancement of digital technology has significantly transformed the operational landscape of financial institutions, including Islamic banks. In the digital era, the implementation of strategic management plays a vital role in maintaining competitiveness and improving organizational performance. This study aims to analyze how strategic management practices can enhance the competitiveness of Islamic banks amid digital transformation. The analysis is based on a review of various national journals focusing on digitalization, product innovation, service quality, and human resource adaptation within Islamic financial institutions. The findings indicate that the success of Islamic banks in facing digital challenges is highly influenced by their ability to integrate technology, develop human resource competencies, and uphold Sharia principles in every innovation. Effective digital strategies not only improve operational efficiency but also strengthen customer loyalty and expand market reach. Therefore, optimizing technology-based strategic management is a key factor in reinforcing the competitive position of Islamic banks in the digital era.